Product inhibition of whey lactose hydrolysis - Demirhan, Elcin; Apar, Dilek Kilic; Ozbek, Belma (TAYLOR & FRANCIS INC, 2008)
In the present study, glucose and galactose inhibition effects for beta-galactosidase hydrolyzing lactose recovered from whey were investigated. The experiments were carried out in 250 mL of 25 mM phosphate buffer solution containing 1, 1.5, 2, 4, and 6% (w/v) lactose recovered from whey by using a commercial beta-galactosidase produced from Kluyveromyces marxianus lactis at a constant temperature of 37 degrees C, pH 6.5, and enzyme concentration of 1 mL/L, in a batch reactor system. The amounts of glucose and galactose added to the reaction solution were 6.25, 12.5, and 25 g/L. A second-order kinetic expression effectively simulated the data of residual lactose concentration with respect to processing time for each experimental condition examined. The Lineweaver-Burk plots showed that the inhibition effects of glucose and galactose were uncompetitive. The inhibition constants (K-i) obtained for glucose and galactose (10.32 g/L and 13.03 g/L, respectively) showed that the glucose was the most effective inhibitor for beta-galactosidase.
Keywords: beta-galactosidase; hydrolysis; inhibition kinetic; whey lactose; IMMOBILIZED BETA-GALACTOSIDASE; ASPERGILLUS-NIGER; SUPPORTS; CHITOSAN; FRAGILIS; KINETICS; REACTOR; Engineering